Temperature dependence of radical recombination luminescence of zinc-sulfur crystalline phosphors; Korus 2004; Vol. 2 - Tyurin Yu. I. Yuri Ivanovich (2004, 2004)
The experiment results on temperature dependence of stationary intensity of PL (photoluminescence) and RRL (radical recombination luminescence) of ZnS-Cu and ZnS-Ag bands excited by hydrogen atoms are being discussed. It was established that the temperatures curves of corresponding PL and RRL ZnS-Cu and ZnS-Ag bands are appreciatively different The temperature curves of PL ZnS-Cu and ZnS-Ag are the conventional curves of luminescence temperature extinguishing. The temperature curves of RRL ZnS-Cu blue and green bands have a maximum and are strongly different from those of PL. Temperature dependence of RRL ZnS-Cu light-blue and green bands are monotonous (like PL) but more sharply following down curves. The observed discrepancy of temperature dependence of RRL and PL ZnS-Cu and ZnS-Ag bands is due to the fact that in case of RRL opposite to volume photo excitation (the excitation depth is sufficiently great 1 mkm), the excited flashing centers are distributed either on the surface or inside a thin surface layer of the thickness not greater than several lattice parameters. Thus the discrepancy between RRL and PL is due to adsorption-deadsorption process on the interface of a crystal phosphor. It was proved that during atomic excitation luminescence as well as photoluminescence, the recombination interaction of flashing centers dominates. It leads with temperature to depositing of greater part of energy in long wave bands. In the process of RRL in comparison with PL, that effect is much greater.